KLASIFIKASI CITRA DALAM IDENTIFIKASI KOL DAN WORTEL MENGGUNAKAN ALGORITMA LDA DAN KNN - Ali Nurdiansyah; Hadrian Erlanda; Syafril Syafril; Yesi Betriana Roza; Rini Sovia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Agriculture is an important sector in the Indonesian economy, where vegetables such as cabbage (Brassica oleracea var. capitata) and carrots (Daucus carota subsp. sativus) play a significant role in meeting the nutritional needs of the community. With the increasing demand for fresh vegetable products, it is important to ensure accurate and efficient identification of these types of vegetables. Mistakes in identification can result in economic losses and affect the quality of products reaching consumers. Image processing technology and machine learning algorithms offer promising solutions to this problem. Image classification, which involves visual analysis of vegetable images, can be used to identify species based on features extracted from the image. Based on these problems, researchers are interested in conducting research on image classification of 2 types of vegetables, namely cabbage and carrots using the KNN and LDA algorithms. From this system, the accuracy results of the classification of green cabbage, purple cabbage and carrots using the KNN and LDA methods were 92.8571%. This research is expected to provide new insights into the use of modern technology to support the preservation and utilization of vegetable types and sustainability.Â Keyword: Hybrid Intelligence System; Vegetable Classification; Image Processing; LDA; KNN Abstrak: Pertanian merupakan sektor penting dalam perekonomian Indonesia, di mana sayuran seperti kubis (Brassica oleracea var. capitata) dan wortel (Daucus carota subsp. sativus) memiliki peran signifikan dalam memenuhi kebutuhan gizi masyarakat. Dengan meningkatnya permintaan akan produk sayuran segar, penting untuk memastikan identifikasi yang akurat dan efisien terhadap jenis-jenis sayuran ini. Kesalahan dalam identifikasi dapat mengakibatkan kerugian ekonomi dan mempengaruhi kualitas produk yang sampai ke konsumen. Teknologi pemrosesan citra dan algoritma pembelajaran mesin menawarkan solusi yang menjanjikan untuk masalah ini. Klasifikasi citra, yang melibatkan analisis visual dari gambar sayuran, dapat digunakan untuk mengidentifikasi spesies berdasarkan fitur-fitur yang diekstraksi dari citra tersebut. Berdasarkan permasalahan tersebut maka peneliti tertarik untuk melakukan penelitian mengenai klasifikasi citra 2 jenis sayuran yaitu kol dan wortel menggunakan algoritma KNN dan LDA. Dari sistem tersebut didapatkan hasil akurasi dari klasifikasi jenis sayur kol hijau, kol ungu dan wortel menggunakan metode KNN dan LDA sebesar 92.8571 %. Penelitian ini diharapkan dapat memberikan wawasan baru dalam penggunaan teknologi modern untuk mendukung pelestarian dan pemanfaatan jenis sayur dan berkelanjutan.Â Kata kunci: Hybrid Intelligence System; Klasifikasi Sayur; Pengolahan Citra; LDA; KNN